In situ formation of oxygen-deficient WO3-x nanosheets for enhanced photocatalytic activity in water splitting and plastic reforming - Xu, Yangsen (2025)
Photocatalytic pathways are essential for the sustainable production of chemicals and fuels, pivotal for achieving a pollution-free planet. Electron-hole recombination is a critical problem that has, so far, limited the efficiency of the photocatalytic materials. Here, oxygen-deficient WO3-x nanosheets were in situ grown in a polymeric carbon nitride (PCN) support during the thermal polycondensation of melamine. The introduction of defect in WO3-x, accompanied by spin polarization and the formed WO3-x/PCN heterostructure, greatly accelerated the charge separation and transfer. The synthesized WO3-x/PCN composite exhibited a tenfold increase in hydrogen generation activity than pure PCN under visible-light (420 ≤ λ ≤ 780 nm). The WO3-x/PCN also demonstrated consecutive 24 h and stable photocatalytic H2 production in the aqueous plastic-containing [poly(vinyl alcohol) (PVA), poly(ethylene terephthalate) (PET) and the PET bottle] solutions under visible light. The hydrogen production rates were determined to be 111.2, 50.5, and 7.8 μmol·h−1·g−1 in PVA, PET and PET bottle, respectively. In addition, the oxygen vacancies WO3 with their localized surface plasmon resonance effect, facilitated efficient utilization of NIR photon and the hydrogen evolution rate over WO3-x/PCN reached to 120 μmol h−1·g−1 under NIR light (700 ≤ λ ≤ 780 nm). This research not only advances the potential applications of WO3-x/PCN in sustainable energy production but also provides insights into environmental remediation through the conversion of plastic wastes.